2011
DOI: 10.2147/hmer.s7860
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger receptor class B member 1 protein: hepatic regulation and its effects on lipids, reverse cholesterol transport, and atherosclerosis

Abstract: Scavenger receptor class B member 1 (SR-BI, also known as SCARB1) is the primary receptor for the selective uptake of cholesterol from high-density lipoprotein (HDL). SR-BI is present in several key tissues; however, its presence and function in the liver is deemed the most relevant for protection against atherosclerosis. Cholesterol is transferred from HDL via SR-BI to the liver, which ultimately results in the excretion of cholesterol via bile and feces in what is known as the reverse cholesterol transport p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 139 publications
(178 reference statements)
0
9
0
Order By: Relevance
“…The SR-BI receptor is associated with lipid metabolism and participates in the bidirectional transport of cholesterol between cells and HDL. Increased clearance of HDL-CE from plasma and enhanced reverse cholesterol transport have been shown to significantly reduce atherosclerosis in animal models[ 23 ]. Previous studies have confirmed that the extracellular domain of SR-BI is critical for its receptor function[ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SR-BI receptor is associated with lipid metabolism and participates in the bidirectional transport of cholesterol between cells and HDL. Increased clearance of HDL-CE from plasma and enhanced reverse cholesterol transport have been shown to significantly reduce atherosclerosis in animal models[ 23 ]. Previous studies have confirmed that the extracellular domain of SR-BI is critical for its receptor function[ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, few reports on virus entry and host genomic SNPs have been published[ 22 ]. For SR-BI, researchers have focused on its regulation of HDL-cholesterol and other metabolites, and a very recent report showed that polymorphisms in the SR-BI gene are associated with the virological response in HCV-infected patients[ 23 , 24 ]. According to the results of a GWAS (genome-wide association study) of 10000 individuals, SNPs in the SR-BI gene are associated with a small, but significant elevation in plasma HDL-cholesterol levels[ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the effect of SR-BI protein was independent of HDL-C levels 24 , the non-lipid pathways, such as affecting endothelial function 25 or inflammatory pathways 26 , have been hypothesized to be the functional mechanisms of rs10846744 variant. Interestingly, recent studies also demonstrated an interaction between glucose metabolism and the expression of SR-BI 27 28 through a transcriptional regulatory mechanism 29 30 . In comparison with the euglycemic control rats, administration of glucose could significantly decrease the hepatic expression of SR-BI in diabetic rats 29 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies also demonstrated an interaction between glucose metabolism and the expression of SR-BI 27 28 through a transcriptional regulatory mechanism 29 30 . In comparison with the euglycemic control rats, administration of glucose could significantly decrease the hepatic expression of SR-BI in diabetic rats 29 30 . In our study, we found that the rs10846744 GG genotype was significantly associated with a higher fasting blood glucose level in subjects with HCV infection, but not in controls.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, less selective cholesteryl ester uptake from HDL particles (~20 %) is found in the liver of cholesteryl ester transfer protein (CETP)-expressing animals (Goldberg et al 1991 ). Hepatic SR-BI expression is regulated by dietary, hormonal, and pharmacological interventions; for reviews see (Kent and Stylianou 2011 ) (Landschulz et al 1996 ; Fluiter et al 1998 ; Serougne et al 1999 ).…”
Section: Introductionmentioning
confidence: 99%